ACCELERATING THE USE OF EDUCATIONAL TECHNOLOGY: A PRACTICAL APPROACH TO ICT SUPPORT AT SD INPRES 3 TALISE - Patmasari, Andi; Ismail, Muhammad; Saadillah, Andi; Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
SD Inpres 3 Talise, located in the Palu Disaster Alert Area, was the target of the community service activity "Accelerating the Use of Educational Technology: A Practical Approach to ICT Mentoring and Empowerment in PMM" aims to improve teachers' ICT capabilities to implement innovative and effective learning methods. Canva and artificial intelligence applications will be covered in in-depth training and mentoring sessions in this project. More than 80 percent of the teachers were successful in using technology, according to the post-training evaluation, which showed a great improvement from the initial condition. With contract number Manual.164/E5/DT.05.00.2024, the project funded by the Directorate of Research, Technology and Community Service (DRTPM) aims to support the improvement of teaching quality. It also prepares teachers to face contemporary education challenges and improves education resilience in disaster-prone areas.